Between Messianism and Zionism—The Religious Proto-Zionists: Transforming from Theurgic-Symbolic Messianism to Zionist Activism - Asaf Yedidya (Religions, 2022)
The 19th century, which began with the immigration to Eretz Israel of 511 disciples of the Vilna Gaon (HaGra) and their families from Lithuania for religious reasons between 1808–1811, ended with the arrival of tens of thousands of Hovevei Zion from Russia and Romania for nationalistic motives, beginning in 1882.This article deals with the differences between the doctrine of redemption of the Vilna Gaon’s disciples and the Zionist ideology of Hovevei Zion in light of the thought of the religious proto-Zionists. Rabbi Zvi Hirsch Kalischer and Rabbi Eliyahu Guttmacher who were the proto-Zionists actually served as transformers from theurgic-symbolic messianic activism to realistic Zionist activism through their combined adoption of all these active approaches and the shift in emphasis from the symbolic to the realistic. Putting them all in the traditional messianic camp or the modern national camp distorts the picture. The great innovation of their doctrine was the transformation of the idea.